Mouth rinsing carbohydrates serially does not improve repeated sprint time - Tomko, P. M.; Laurent, C. M.; Fullenkamp, A. M.; Voth, N. R.; Young, C. A. (Journal of Human Kinetics, 2019)
Sensing carbohydrates via the oral cavity benefits performance outcomes during brief high intensity bouts of exercise. However, the extent to which carbohydrates need to be present in the oral cavity to influence sprint performance is less understood. The purpose of this study was to determine if serial increases in carbohydrate rinse time across sprint sets attenuates increases in sprint time compared to no serial increases in carbohydrate rinse time across sprint sets. Fifteen sprint trained participants completed three repeated anaerobic sprint tests (RAST), 3 sets of 6 x 35-m sprints, under two different carbohydrate mouth rinsing (CMR) conditions; (1) rinsing for only 5 seconds (s), and (2) rinsing for 5 s, 10 s and 15 s (serial rinse). Prior to a RAST, participants provided perceived recovery status (PRS) and perceived feeling of arousal (FAS). Upon completion of each individual sprint, participants gave a rating of perceived exertion (RPE). A lactate sample was taken upon completion of each individual sprint set and after all 3 RASTs a session rating of perceived exertion (S-RPE) was measured. There were no significant differences in peak (p = 0.18) and average sprint time (p = 0.41). There were no significant differences in perceptual measures: RPE, PRS, FAS, S-RPE or for blood lactate concentration between CMR conditions. Overall, serial rinsing resulted in changes that were most likely trivial, but showed a 50% chance in perceiving a sprint session as less difficult. Rinsing carbohydrates in a serial manner between repeated sprint sets produces trivial changes of sprint speed and perceptual measures from sprint performance.